Sharp recanalization and rendezvous technique for biliary occlusions due to spacious bile leak after hepatectomy. (17th June 2021) - Hirata, Hajime; Kuwatani, Masaki; Abo, Daisuke
Abstract : Highlight Hirata and colleagues report on a difficult case of biliary strictures and extensive bile leak near the hepatic hilum after hepatectomy for metastatic cancer. Treatment with sharp recanalization and the rendezvous technique was effective to establish bridging between the common bile duct and intrahepatic bile duct in this case.